Activation of a floral homeotic gene in Arabidopsis. - Busch, MA; Bomblies, K; Weigel, D.
The patterned expression of floral homeotic genes in Arabidopsis depends on the earlier action of meristem-identity genes such as LEAFY, which encodes a transcription factor that determines whether a meristem will generate flowers instead of leaves and shoots. The LEAFY protein, which is expressed throughout the flower, participates in the activation of homeotic genes, which are expressed in specific regions of the flower. Analysis of a LEAFY-responsive enhancer in the homeotic gene AGAMOUS indicates that direct interaction of LEAFY with this enhancer is required for its activity in plants. Thus, LEAFY is a direct upstream regulator of floral homeotic genes.